Modelling construction processes: a review of research and dissertations at the Poznań University of Technology = Modelowanie procesów budowlanych: przegląd badań oraz dysertacji realizowanych w Politechnice Poznańskiej - Kapliński, Oleg (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The achievements, grants and awards presented to the Chair of Construction Engineering and Construction Management at PUT in the field of modelling of construction processes are reviewed in the article. The needs of phenomena analysis (e.g. waiting, equilibrium), use of the induction method and an application of hybrid methods have been indicated in the review of the problems and modelling methods. Selected areas, mainly of research published abroad by our authors, have been analysed among other publications in context of discussion of research areas.
Keywords: modelowanie procesów budowlanych; procesy budowlane; Politechnika Poznańska; construction management; construction engineering; modelling of processes; application of mathematical methods; hybrid methods